2016
DOI: 10.1007/s11481-016-9720-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Treatment Attenuates Neuroinflammation and Dopaminergic Neurodegeneration in an Animal Model of Parkinson’s Disease, Shifting M1 to M2 Microglia Responses

Abstract: Microglia-mediated neuroinflammation has been described as a common hallmark of Parkinson's disease (PD) and is believed to further exacerbate the progressive degeneration of dopaminergic neurons. Current therapies are unable to prevent the disease progression. A significant association has been demonstrated between PD and low levels of vitamin D in patients serum, and vitamin D supplement appears to have a beneficial clinical effect. Herein, we investigated whether vitamin D administered orally in a 1-methyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 59 publications
6
87
0
1
Order By: Relevance
“…A post-mortem study showed the increased levels of TNF-α and other inflammatory mediators in the brain of Parkinson’s disease patients [76]. VD3 was shown to significantly attenuate the loss of TH-positive neuronal cells, microglial cell activation, iNOS expression, among other typical hallmarks of microglia activation, in an animal model of PD similar to ours [75]. …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A post-mortem study showed the increased levels of TNF-α and other inflammatory mediators in the brain of Parkinson’s disease patients [76]. VD3 was shown to significantly attenuate the loss of TH-positive neuronal cells, microglial cell activation, iNOS expression, among other typical hallmarks of microglia activation, in an animal model of PD similar to ours [75]. …”
Section: Discussionsupporting
confidence: 60%
“…In the last decades, neuroinflammation has been considered an important cause for progression of PD [73, 74]. In the MPTP-induced PD model, researchers demonstrated that the treatment with VD3 attenuates iNOS and pro-inflammatory cytokines expression [75]. The same pattern could be observed in animal models using the 6-OHDA neurotoxin.…”
Section: Discussionmentioning
confidence: 88%
“…Calvello et al . recently showed that administration of vitamin D to methylphenyltetrahydropyridine‐intoxicated mice, attenuated neuronal loss, microglial activation, iNOS and TLR4 expression and upregulated anti‐inflammatory cytokines IL‐10, IL‐4 and TGF‐ β .…”
Section: Immunomodulatory Therapies For Parkinson′s Diseasementioning
confidence: 99%
“…Another group demonstrated in a mouse model of PD, that blocking NF-jB signalling improved motor deficits, alleviated neuronal necrosis, decreased the expression of pro-inflammatory cytokines IL-6 and IL-1b and antagonized microglia-induced neuroinflammation [61]. Calvello et al [62] recently showed that administration of vitamin D to methylphenyltetrahydropyridine-intoxicated mice, attenuated neuronal loss, microglial activation, iNOS and TLR4 expression and upregulated anti-inflammatory cytokines IL-10, IL-4 and TGF-b.…”
Section: Alternative Immune Therapies For Parkinson 0 S Diseasementioning
confidence: 99%
“…Relevant research however, has not reached consistent conclusions, with some studies indicating that fats and fatty acids also have protective effect on neurons, and can reduce the risk of disease. Furthermore, studies have tentatively shown that estrogen and non-steroidal anti-inflammatory drugs may also have protective functions [11][12][13]. Based on the above, inhibition of oxidative stress may be an important way of alleviating and preventing PD.…”
Section: Introductionmentioning
confidence: 98%